THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) TOOLS IN TEACHING ENGLISH THROUGH AN INTEGRATED APPROACH (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The rapid emergence of Artificial Intelligence (AI) in education has transformed English language teaching by offering new opportunities for personalized instruction, multimodal interaction, and skill integration. This article investigates the role of AI tools in supporting an integrated approach to English teaching, in which reading, writing, listening, speaking, and critical thinking are developed holistically. The study argues that AI enhances the efficiency, quality, and accessibility of integrated language learning through adaptive feedback, intelligent tutoring systems, automated assessment, and content-generation mechanisms. Despite these benefits, challenges such as digital inequality, teacher readiness, ethical considerations, and overreliance on AI remain critical concerns. The findings suggest that with thoughtful pedagogical planning, AI can become a powerful component of integrated English instruction, promoting learner autonomy and improving language competence in technology-enhanced environments.